Pengaruh Kegiatan Mewarnai Terhadap Perkembangan Motorik Halus Di KB Salomo Surabaya - Trifena Ayu Permata Sari; Ujang Maulana Yusup (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of coloring activities on the development of fine motor skills in children at KB Salomo Surabaya. The method used is Classroom Action Research consisting of two cycles. The subjects were 10 children aged 4–5 years. Each cycle included the stages of planning, implementation, observation, and reflection. The results showed an improvement in fine motor skills after the children participated in structured coloring activities. In the pre-cycle stage, only 2 children (20%) were in the “good” category, 3 children (30%) in “fair,” and 5 children (50%) in “poor.” After Cycle I, the number of children in the “good” category increased to 3 (30%), “fair” to 4 (40%), and “poor” decreased to 3 (30%). In Cycle II, development improved further: 5 children (50%) were in the “good” category, 4 (40%) in “fair,” and only 1 child (10%) remained in the “poor” category. In conclusion, coloring activities have a positive effect on improving children's fine motor skills. This activity helps children control hand movements and strengthens fine motor coordination in an enjoyable and effective way. Therefore, coloring can be used as an alternative learning strategy in early childhood education.